Do Growth-Option Firms Use Less Relative Performance Evaluation? - Albuquerque, Ana Maria (The Accounting Review, 2014)
ABSTRACT The use of relative performance evaluation (RPE) in compensation contracts for CEOs at growth-option (GO) firms that operate in more volatile environments can provide insurance against common exogenous shocks and thus reduce the amount of risk that CEOs face. However, the implementation of RPE for high-GO firms can be impaired by these firms' inability to find a peer group that captures common risk exposure. This paper studies GO firms' reliance on RPE and finds that the use of RPE in CEO compensation contracts varies negatively with a firm's level of growth options. The tests use three proxies for growth options: the market-to-book value of assets, research and development expenses scaled by assets, and a factor obtained from a principal component analysis. The results are robust to controlling for the impact of other firm characteristics on pay-for-performance sensitivities. Data Availability: All data are obtained from publicly available sources.